Designing understandable, action-oriented, and well-perceived earthquake risk maps—The Swiss case study - Dallo, Irina; Schnegg, Laura N.; Marti, Michèle; Fulda, Donat; Papadopoulos, Athanasios N.; Roth, Philippe; Danciu, Laurentiu; Valenzuela, Nadja; Wenk, Simon R.; Bergamo, Paolo; Haslinger, Florian; Fäh, Donat; et al. (Frontiers in Communication, 2024)
With seismic risk assessments becoming more available and reliable over the last years, the need to communicate seismic risk emerged. Seismic risk allows people to understand what impacts earthquakes can have and how they could affect their lives. In Switzerland, a nation-wide seismic risk model (ERM-CH23) was published in 2023 demanding sophisticated communication products to inform about its results. Since only limited research has been conducted on how to best communicate earthquake risk information to societies including the general public, key elements of the outreach activities were tested before the model release. To this end, we, an interdisciplinary group, conducted a nationwide survey in Switzerland in December 2022 to test different earthquake risk map designs by varying the color scale and the legend type. We analyzed the effects of the map and legend design on people’s correct interpretation of the risk information, perceived usefulness, risk perception, and motivation to take action. Our survey revealed that (i) a legend with the combination of qualitative and quantitative labels leads to more accurate interpretations of the information presented on the map and is preferred by the public; (ii) the color scale determines how people perceive the spatial risk; and (iii) personal factors influence people’s interpretation skills, risk perception, and intention to take action. Our study thus provides insights and recommendations on how to best design user-centered earthquake risk maps as a key outreach product to ensure their effective use by the public, consequently enhancing society’s resilience to earthquakes in the long term.